The effect of learning with direct playing style on the accuracy of table tennis serve in 8-10-year-old players - Jalal Obaid , Ali; Hussein , Loaiy; Mhawes Zighair , Raid (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the effect of learning with direct playing style in developing the accuracy of table tennis serve in 8-10-year-old players. The researchers used the experimental method in the style of two equal groups for its suitability to the nature of the research. The research sample was determined by 18 table tennis players (aged 8-10 years old), from the specialized school in the Ministry of Youth and Sports, Baghdad, for the academic year 2021. We randomly divided the sample into two equal groups (experimental and control), each group comprising 6 players. The experimental group used the direct playing method, while the control group used the traditional method. In order to determine the skill test for the accuracy of the table tennis serve skill in the sample, the researchers used the test of the accuracy of the table tennis serve. The results of our study showed that there were statistically significant differences between the pre- and post-test results for the experimental group on the study variable, in favor of the post-test (t = 6.27, p < 0.05). We also found statistically significant differences in the results of the pre- and post-test results for the control group, in favor of the post-test (t = 5.16, p < 0.05). We also had statistically significant differences between the experimental and control group in the post-test results, in favor of the experimental group (t = 5.34, p < 0.05). In conclusion, the utilization of direct playing method had a constructive outcome in acquiring fundamental abilities. The specialists are recommended to embrace this instructive technique for fledglings to gain proficiency with the essential abilities of table tennis.